2000
DOI: 10.1002/1529-0131(200011)43:11<2397::aid-anr4>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Combination drug therapy retards the development of rheumatoid atlantoaxial subluxations

Abstract: Objective. To compare the efficacy of combination therapy with disease-modifying antirheumatic drugs (DMARDs) versus single therapy with DMARDs in the prevention of early cervical spine changes in patients with rheumatoid arthritis (RA).Methods. One hundred ninety-five patients with recent-onset RA (mean disease duration 8 months) were randomly assigned to receive a combination of DMARDs (sulfasalazine, methotrexate, hydroxychloroquine, and prednisolone) or a single DMARD with or without prednisolone. After 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 14 publications
3
46
0
9
Order By: Relevance
“…1 Nonoperative treatment has been shown to provide some benefits to these patients, but studies have been limited by small sample sizes, minimal follow-up data, and lack of control groups. [2][3][4][5][6][7] Additionally, these studies examined the immediate and short-term effects of these interventions without long-term outcome data for patients who eventually undergo surgery. For example, Manchikanti et al 8 performed a randomized study in which patients with chronic axial neck and radicular pain, attributed to cervical disc herniations, received cervical epidural injections with local anesthetic with or without corticosteroids.…”
Section: Introductionsupporting
confidence: 62%
“…1 Nonoperative treatment has been shown to provide some benefits to these patients, but studies have been limited by small sample sizes, minimal follow-up data, and lack of control groups. [2][3][4][5][6][7] Additionally, these studies examined the immediate and short-term effects of these interventions without long-term outcome data for patients who eventually undergo surgery. For example, Manchikanti et al 8 performed a randomized study in which patients with chronic axial neck and radicular pain, attributed to cervical disc herniations, received cervical epidural injections with local anesthetic with or without corticosteroids.…”
Section: Introductionsupporting
confidence: 62%
“…We reported earlier that combination therapy with traditional DMARDs retarded the early development of atlantoaxial subluxations over 2 years (5). In the present study, we found a low long-term prevalence of cervical spine subluxations in patients who were treated early and continuously with traditional DMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that up to 42% of patients treated with conventional therapy exhibit aAAS, AAI, or SAS after 20 years of RA (4). We also recently showed that aggressive treatment of RA with a combination of disease-modifying antirheumatic drugs (DMARDs) retards or prevents early development of atlantoaxial subluxations (5). However, very little is known of the long-term prevalence of RArelated cervical spine changes in patients who are treated actively with DMARDs from the time of diagnosis.…”
mentioning
confidence: 99%
“…Frente a la presencia de compromiso radiológico progresivo, o deterioro neurológico, se debe considerar el tratamiento quirúrgico2,11. Adicionalmente, existen estudios que sugieren que, el tratamiento precoz con drogas antirreumáticas modificadoras de la enfermedad es capaz de prevenir o retardar el desarrollo de alteraciones a nivel atlanto-axial 18,19 . Las indicaciones quirúrgicas incluyen: presencia de inestabilidad, déficit neurológico y dolor cervical intratable 2,11 Frente a la presencia de déficit neurológico o de dolor intratable, la indicación quirúrgica es clara.…”
Section: Imagenologíaunclassified
“…relación a la recuperación neurológica. Uno de los predictores Frente a la presencia de compromiso radiológico progresivo, de recuperación post operatoria más importante es la condicio deterioro neurológico, se debe considerar el tratamiento ren que, el tratamiento precoz con drogas antirreumáticas modificadoras de la enfermedad es capaz de prevenir o retardar el desarrollo de alteraciones a nivel atlanto-axial 18,19 .…”
Section: Tratamientounclassified